PENGARUH CORPORATE GOVERNANCE TERHADAP INVESTASI RESEARCH & DEVELOPMENT PADA PERUSAHAAN FARMASI DI INDONESIA - Cahyo Utomo, Ulul Albab; Septiani, Aditya (Diponegoro Journal of Accounting, 2017)
Deciding the investment scale of a company's Research & Development is a strategic investment decision related to creating long-term value of the company and it is a very important decision because it has a certain level of risk and the cost is not small. Corporate governance of a company differs according to the ownership structure of each company, and corporate governance will affect the company's decision-making. The purpose of this study is to examine the effect of corporate governance structure, namely majority shareholder, board of directors, and independent commissioner to investment research & development at pharmaceutical company listed in Indonesian Stock Exchange period 2008 to 2015.The population of this study is a pharmaceutical company listed on the Indonesia Stock Exchange. The number of pharmaceutical companies listed during the period 2008 to 2015 is as many as 10 companies. By using purposive sampling, obtained a sample of 4 companies. Data analysis technique used in this research is multiple linear regression analysis.The results in this study indicate that majority shareholders have negatively insignificant influence on research & development investment. Meanwhile, the board of directors has a significant negative impact on investment research & development. And the independent commissioners has an insignificant positive effect on investment & development investment.